2003
DOI: 10.1002/pi.1093
|View full text |Cite
|
Sign up to set email alerts
|

Part 7. Effects of poly(L‐lactide‐co‐ϵ‐caprolactone) on morphology, structure, crystallization, and physical properties of blends of poly(L‐lactide) and poly(ϵ‐caprolactone)

Abstract: Blended films of poly(L-lactide) [ie poly(L-lactic acid)] (PLLA) and poly(ε ε ε ε ε ε-caprolactone) (PCL) without or mixed with 10 wt% poly(L-lactide-co-ε ε ε ε ε ε-caprolactone) (PLLA-CL) were prepared by solution-casting. The effects of PLLA-CL on the morphology, phase structure, crystallization, and mechanical properties of films have been investigated using polarization optical microscopy, scanning electron microscopy, differential scanning calorimetry and tensile testing. Addition of PLLA-CL decreased num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 30 publications
(48 reference statements)
2
73
0
Order By: Relevance
“…An improvement of the toughness of such brittle polymers can generally be achieved by blending a ductile secondary phase into the base polymer. PCL, a ductile biodegradable polymer, has been chosen as a blending partner for PLA, [10][11][12][13][14][15] and the fracture properties of PLA/PCL are found to be greater than those of pure PLA. However, it is also found that the immiscibility of PLA and PCL causes phase separation, and tends to lower the fracture properties.…”
Section: Introductionmentioning
confidence: 99%
“…An improvement of the toughness of such brittle polymers can generally be achieved by blending a ductile secondary phase into the base polymer. PCL, a ductile biodegradable polymer, has been chosen as a blending partner for PLA, [10][11][12][13][14][15] and the fracture properties of PLA/PCL are found to be greater than those of pure PLA. However, it is also found that the immiscibility of PLA and PCL causes phase separation, and tends to lower the fracture properties.…”
Section: Introductionmentioning
confidence: 99%
“…In general, a blend of immiscible polymers such as PLLA and PCL creates macro-phase separation of the two components due to difference of solubility parameter. This kind of phase separation dramatically affects the physical and mechanical properties of the blend (Dell'Erba et al, 2001;Maglio et al, 1999;Tsuji et al, 2003). Dependence of PCL content on the critical energy release rate at crack initiation, G in , is shown in Fig.9.…”
Section: Fracture Behavior Of Pla/pcl Blendmentioning
confidence: 99%
“…Blending with ductile biodegradable polymers such as PCL (Broz, 2003;Dell'Erba, 2001;Chen, 2003;Todo, 2007;Tsuji, 1996Tsuji, , 1998Tsuji, , 2001Tsuji, , 2003, poly(butylene succinate-co-ε-caprolactone) (PBSC) (Vannaladsaysy, 2010) and poly (butylene succinate-co-L-lactate) (PBSL) (Shibata, 2006(Shibata, , 2007Vannaladsaysy, 2009;Vilay, 2009) has extensively been investigated in order to improve the fracture energy of PLA. Amoung of them, PCL is known to be bioabsorbable and bioaabsorbable, therefore has been applied in medical fields.…”
Section: Fracture Behavior Of Pla/pcl Blendmentioning
confidence: 99%
See 1 more Smart Citation
“…Its importance has led to many studies on its mechanical properties and fracture behavior [3][4][5][6][7] which found that the fracture behavior of PLA is relatively brittle in nature. Therefore, blending with ductile biodegradable polymers such as poly (ε-caprolacton) (PCL) has been adopted to improve the fracture properties [8][9][10][11][12][13][14]. Although PCL blend increases the fracture energy of neat PLA, it was also found that the polymer blend exhibits phase separation as a result of the immiscibility of the polymers [9].…”
Section: Introductionmentioning
confidence: 99%